A tactical multi-objective multi-product green supply chain planning optimization model - S. Al-Ashhab, M.; A. Mlybari, E (International Journal of Engineering and Technology, 2019)
In this paper, a Multi-objective, multi-products, and multi-period green supply chain optimization model that consider some important economic and environmental risks and their associated impacts are developed using the lexicographic procedure. Managing the impacts of both side of economic and environmental risks, maximizing opportunities’ impacts and minimizing threats’ impacts. Economic impacts include maximizing profit, maximizing the overall service level while minimizing the total cost, and the environmental impacts include minimizing energy consumption and minimizing CO2 emissions from transportation operations. The model considers transportation mode selection (Heavy or light trucks). The model efficacy has been proved through results discussion. Moreover, the effect of different allowable deviation on the objectives is discussed.
Keywords: Green Supply Chain; Multi-Objective; Production Planning; Goal Programming; Multi-Products; Risk; Transportation Modes.